(untitled) (Journal of Environmental Science Studies, 2022)
Taking the author’s experience as an example, this research tries to discuss the possible connection and relationships between food consumption with our attitude, behaviour, personality, psychology, emotion and social identity, and therefore to reflect on how food affects our daily life.